Is Confucianism compatible with autonomous learning? An investigation of cultural influences on self-regulated learning in China - Schenck, Andrew; Zhang, Caiyun (Frontiers in Education, 2025)
IntroductionCultural values may impact how well a learner uses self-regulated learning strategies in Confucian contexts, yet research remains limited.MethodsTo address the gap in past research, surveys were given to 281 Chinese university students concerning preferences for Confucian values, self-regulated learning, and self-regulated use of technology. Confucian values were then statistically compared to preferences for self-regulated learning and use of technology using regression and Pearson correlations.ResultsResults suggest that traditional cultural values that promote collectivism and power distance significantly impact perspectives on self-regulated learning. However, these same cultural values do not appear to significantly influence perspectives on self-regulated use of technology. Whereas conceptions about learning have been clearly defined by long-standing Confucian traditions, perspectives on new educational technology have not, explaining the findings.ConclusionNew techniques may be developed to enhance self-regulated learning in Confucian heritage countries. Educational techniques that mirror collective cultural beliefs and respect norms for power distance may enhance performance in the classroom.